2015
DOI: 10.1364/oe.23.009690
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface acoustic waves by stroboscopic white-light interferometry

Abstract: We present phase-sensitive absolute amplitude measurements of surface acoustic wave fields obtained using a stroboscopic white-light interferometer. The data analysis makes use of the high resolution available in the measured interferometric phase data, enabling the characterization of the out-of-plane surface vibration fields in electrically excited microstructures with better than 100 pm amplitude resolution. The setup uses a supercontinuum light source with tailored spectral properties for obtaining the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…White light interference has been widely used for the accurate measurement of microstructures due to its non-contact high sensitivity and large measurement range. [213][214][215] The traditional rainbow is a non-coherent optical phenomenon, which is mainly caused by the different refractive index of water with different Intensity distributions in the case of (h)-(j). Reproduced with permission.…”
Section: Coherent Rainbows With White Light Lasermentioning
confidence: 99%
“…White light interference has been widely used for the accurate measurement of microstructures due to its non-contact high sensitivity and large measurement range. [213][214][215] The traditional rainbow is a non-coherent optical phenomenon, which is mainly caused by the different refractive index of water with different Intensity distributions in the case of (h)-(j). Reproduced with permission.…”
Section: Coherent Rainbows With White Light Lasermentioning
confidence: 99%
“…Optical interferometry has the advantages of non-contact, high accuracy, and direct measurement of micro-vibration, so they have been widely used. Common optical interferometry includes homodyne interferometry [1][2][3][4][5][6], heterodyne interferometry [7][8][9][10][11][12], Sagnac interferometry [13] and stroboscopic white light interferometry [14][15][16][17]. Knuuttila, J. V. et al [3] demonstrated a homodyne scanning Michelson interferometer, which can directly measure the surface acoustic wave in the range of 0.5 MHz to 1 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Under the premise of ensuring high accuracy, the maximum measurement is 300 pm. Kokkonen, K. et al [15]…”
mentioning
confidence: 99%
“…In order to address this issue, full-field imaging methods based on diffraction and interferometry polarimetry have been developed to visualize variations of the detection optical wave induced by the acoustic waves [12,13]. By combining with a stroboscopic timing scheme, transient surface acoustic waves have been dynamically visualized with photorefractive interferometry [14] and white-light interferometry [15]. Also, Schlieren photography has been utilized to image the dynamic sound pressure in the air [16,17].…”
Section: Introductionmentioning
confidence: 99%